2008
DOI: 10.1002/prot.21939
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of the DNA‐bound form of a novel tandem repeat DNA‐binding domain, STPR

Abstract: Fibroin-modulator-binding protein 1 (FMBP-1) is a predicted transcription factor of the silkworm fibroin gene. The DNA-binding domain of FMBP-1 consists of four almost perfect tandem repeats of 23 amino acids each (R1-R4), and is referred to as the score and three amino acid peptide repeat (STPR) domain. This characteristic domain is conserved in eukaryotes, but the DNA-binding mode is not known. In this study, the structural properties of the DNA-bound form of the STPR domain were characterized. The combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The preparation of proteins without any tag was carried out as described (7). Crude extract was loaded onto a SP-Sepharose column, and fractionated with a linear gradient from 0 M to 1 M NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of proteins without any tag was carried out as described (7). Crude extract was loaded onto a SP-Sepharose column, and fractionated with a linear gradient from 0 M to 1 M NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Previous findings have suggested that the DNA-binding domains of TFs or DNA repair proteins might enter the groove of a DNA helix during the DNA sliding state; conformational changes in 3D structure are important for such interactions [32,35]. Findings from previous in vitro DNA-binding experiments involving STPR domains indicate that a conformational change into the a-helical-rich structure is important for stable DNA binding and that the R9A mutation abolishes this conformational change [13]. Thus, this conformational change might play an important role during 3rd component movements of the STPR as well as for stable DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of Recombinant STPR Peptides. Recombinant hSTPR and sSTPR peptides were prepared by an Escherichia coli expression system as described previously (13). The nucleotide sequence of the hSTPR domain was amplified using two oligonucleotide primers (5 0 -GGAATTCCATATGATGCGACAGA-ATGAGCCTTTGGAA-3 0 and 5 0 -CCGCTCGAGCATTTTC-TCCAGCCTCCTCTT-3 0 ) and the pOTB7 plasmid including cDNA of human ZNF821 (LOC55565) (purchased from Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%